Modulation of Tumor Cell Survival, Proliferation, and Differentiation by the Peptide Derived from Tenascin-C: Implication of β1-Integrin Activation - Takuya Iyoda; Fumio Fukai (International Journal of Cell Biology)
Cell adhesion to extracellular matrix (ECM) participates in various biological processes, such as cell survival, proliferation, differentiation, and migration. Since these processes are essential for keeping homeostasis, aberration of these processes leads to a variety of diseases including cancer. Previously, we found that a peptide derived from tenascin- (TN-) C, termed TNIIIA2, stimulates cell adhesion to ECM through activation of β1-integrin. It has been shown that TNIIIA2 can modulate cell proliferation and differentiation. Interestingly, TNIIIA2 could not only enhance cell proliferation but also induce apoptotic cell death, depending on cellular context. In this review, we show the function of the peptide TNIIIA2 in cell survival, proliferation, and differentiation and refer to the possibility of new strategy for tumor suppression by regulating cell adhesion status using the ECM-derived functional peptides.